Monetary policy effect in an economy with heavily managed exchange rate - Bui, Thanh Trung (University of Economics Ho Chi Minh City, 2023)
The primary objective of this paper is to investigate the effect of monetary policy on macroeconomic variables in Vietnam, which is a small, open, and developing economy with heavily managed ex-change rate. Monetary policy shock is identified by the sign re-striction methodology. Unlike previous studies, this paper identifies a monetary contraction by a combination of an increase in interest rates, a decrease in central bank credit, a drop in the stock of foreign exchange reserves, and a fall in broad money. The empirical results show that output and prices begin to reduce after a restrictive mone-tary shock in the medium term, suggesting the adverse effect of monetary policy in the short term and the necessity to improve the transparency of monetary setting. Meanwhile, exchange rates are unresponsive to a tightening decision, which is not a sign of puzzle but plausible when the nature of a peg regime is taken into account. Furthermore, foreign exchange policy causes inflation to rise since its effect is partially sterilized by changes in monetary policy instru-ments. Therefore, Vietnamese monetary authorities should consider a shift toward a more floating regime to achieve monetary inde-pendence or foster the development of financial markets in order to alleviate inflationary pressure caused by foreign exchange policy.